INFLUENCE OF ENVIRONMENTAL MANAGEMENT ACCOUNTING, ORGANIZATIONAL STRATEGY, AND GREEN HUMAN RESOURCE MANAGEMENT ON ENVIRONMENTAL PERFORMANCE AND CORPORATE INNOVATION: (A Study of Hazardous Waste Processing Companies in Greater Jakarta) - Miftahul Jannah; Muhammad Irfan Tarmizi; Eva Herianti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The current emphasis on industrial growth in today's society has sparked debates regarding the environment, as concerns about the depletion of natural resources and resulting environmental damage continue to grow. Issues such as climate change, air and water pollution, and the use of hazardous materials highlight the challenges that industries worldwide are facing. Despite advancements in the industry, concerns persist about the environmental impact, leading to a global dialogue on environmental performance. This study seeks to examine the impact of Environmental Management Accounting, Organizational Strategy & Green Human Resource Management on Environmental Performance with Corporate Innovation as a Moderating Variable (Case Study on B3 Waste Management Company). This research adopts a quantitative approach with primary data as the source. The study population consists of B3 Waste Management Companies in Greater Jakarta, and the sample includes Directors, Finance Managers, Marketing Managers, HRD, and Legal Development personnel. The study includes a sample size of 78 employees. Data analysis for this study utilizes the SmartPLS Version 4.0 data analysis method. The research findings and hypothesis testing results indicate that Environmental Management Accounting, Organizational Strategy, and Green Human Resource Management have a positive and significant impact on Environmental Performance. Furthermore, Corporate Innovation strengthens the relationship between Environmental Management Accounting and Environmental Performance. However, Corporate Innovation does not strengthen the relationship between Organizational Strategy and Environmental Performance, nor does it strengthen the relationship between Green Human Resource Management and Environmental Performance. Additionally, Corporate Innovation has a positive and significant effect on Environmental Performance.